Implementation of Time Management Using the Critical Path Method (CPM) in the Construction of School Buildings - Romadhani, Ocarullyta; Badi’ah, Roudlotul; Wicaksono, Arian Yusuf (Jurnal Ekonomi Balance, 2025)
Delays in school building construction projects are a recurring challenge that can significantly impact overall project timelines and budgets. This study aims to analyze time efficiency in project implementation by applying the Critical Path Method (CPM) to identify activities that have the greatest influence on the project's completion time. A descriptive quantitative approach was employed, with primary data collected through interviews and project documentation obtained from CV Prima Karya, a construction company actively involved in school building projects. The research utilized network planning and POM-QM for Windows software to generate a project schedule and calculate the earliest and latest start and finish times, slack, and critical activities. Results indicate that nine key activities lie on the critical path, including preparation, earthwork, foundation, concrete, iron work, roof covering, aluminum, wood, and key-glass installations. Acceleration analysis showed that reducing the project duration from 33 to 30 days increased the overall cost from IDR 179,584,643 to IDR 216,497,434. The cost slope analysis highlighted the additional expenses incurred due to time reduction on critical path tasks. The study concludes that CPM is effective for optimizing project duration and managing potential delays. It is recommended that companies adopt CPM during the planning phase to reduce inefficiencies and cost overruns. Future research should compare CPM with other scheduling techniques such as PERT or Gantt Charts to determine the most effective approach under varying project conditions.